M-PRESS-CreditRisk: A holistic micro- and macroprudential approach to capital requirements - Natalia Tente; Natalja von Westernhagen; Ulf Slopek (Deutsche Bundesbank, 2017)
M-PRESS-CreditRisk is a new top-down macro stress testing framework that can help supervisors gauge banks' capital adequacy related to credit risk. For the first time, it combines calibration of microprudential capital requirements and macroprudential buffers in a unified, coherent framework. Its core element is an advanced credit portfolio model - SystemicCreditRisk - built upon a rich, non-linear dependence structure for interconnected bank portfolios. Incorporating numerous sector/country-specific systematic factors, the model focuses on credit default concentration risk as a major source of large losses that may have systemic impact. A test run using a sample of 12 systemically important German banks provides measures for systemic credit risk and the banks' contributions to it in both baseline and stress scenarios. Capital requirements calibrated to the results combine elements of Pillar 1 and Pillar 2, whereas macroprudential buffers can internalize the system's tail risk. The maximum model-based combined requirements range between 6.3% and 27.2% of credit RWA depending on the bank. A comparison with the reported capital figures suggests that there appears to be enough capital in the banking system, but its distribution might be suboptimal from a systemic point of view as the capital level of a number of banks might need improvement.
Keywords: C15; C23; C63; G21; G28; 330; Systemic Credit Risk; Tail Risk; Stress Testing; Microprudential Capital Requirements; Systemic Risk Buffer; O-SII Buffer; Hierarchical Archimedean Copula